Fine structure of the small-scale solar convection - Kovalchuk, M.M.; Hirnyak, M.B. (Известия Крымской астрофизической обсерватории, 2013)
Simulation of theoretical profiles and equivalent widths of absorption lines in the solar spectrum was carried out by using numerical solution of the radiative transfer equation within limits of the six-component model of the solar atmosphere VAL-80.